The Effect of Profitability, Dividend Policy, Free Cash Flow, and Company Growth on Debt Policy in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 Period - Riniyanti, Titi Hinda; Yusrialis, Yusrialis (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
One of the problems that still occur in Indonesia today is the weakness of the Government Internal Control System (SPIP). This is indicated by the many findings of BPK's examination of weaknesses in the government's internal control system. In this case, there is a role for government internal auditors that are highly expected to create an effective and sustainable control system. This study aims to determine the effect of the role of APIP in implementing the Maturity of the SPIP at the Inspectorate Kab. South Solok. This research is a quantitative. The population and sample in this research were all government internal supervisory apparatus at the Inspectorate Kab. South Solok. Data collection technique used is through a questionnaire. The analysis technique used in this research is descriptive statistical analysis. The instrument were tested using validity test, reliability test, and normality test. Data analysis technique used is multiple linear regression analysis.The results showed that the role of leadership, internal supervisors, consultants, and catalysts had a positive effect on the implementation of the maturity of SPIP. While the role of quality assurance has a negative effect on the implementation of the maturity of SPIP. This study aims to examine the effect of profitability, dividend policy, free cash flow, and company growth on debt policy in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the period 2017–2021. The population consists of 51 companies, with a sample of 18 companies selected using purposive sampling based on specific criteria. The data were analyzed using multiple linear regression with the help of SPSS software.The results show that partially, profitability, free cash flow, and company growth have no significant effect on debt policy. Meanwhile, dividend policy has a positive and significant effect on debt policy. Simultaneously, all four independent variables influence debt policy. This research provides insights for company management and investors to better understand internal factors that affect corporate funding decisions through debt.